An Efficient Palladium‐Catalyzed CH Alkoxylation of Unactivated Methylene and Methyl Groups with Cyclic Hypervalent Iodine (I3+) Oxidants1. Issue 51 (8th November 2013) - Shan, Gang; Yang, Xinglin; Zong, Yu; Rao, Yu
<x xml:space="preserve">Abstract</x> All the hype: The title reaction has been developed for the facile synthesis of a variety of complex alkyl ethers. Cyclic hypervalent iodine (I3+) reagents serve as oxidants for this unique CH alkoxylation reaction. The reaction demonstrates excellent reactivity, good functional‐group tolerance, and high yields. Q=8‐aminoquinoline‐derived auxiliary.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>